Writing and seeing : essays on word and image - Homem, Rui Manuel G. de Carvalho; Lambert, Maria de Fátima (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2006)
The essays in this volume are informed by a variety of theoretical assumptions and of critical methodologies, but they all share an interest in the intersections of word and image in a variety of media. This unifying rationale secures the present collection's central position in the current critical context, defined as it predominantly is by ways of reading that are based on a relational nexus. The intertextual, the intermedial, the intersemiotic are indeed foregrounded and combined in these essays, conceptually as much as in the critical practices favoured by the various contributions. Studies.